A competitive strategy for vegetable products: traditional varieties of tomato in the local market - Brugarolas, M.; Martínez-Carrasco, L.; Martínez-Poveda, A.; Ruiz-Martínez, J.J. (Spanish Journal of Agricultural Research, 2009)
The aim of this article is to analyse whether growing traditional horticultural varieties would be a profitable alternative so farmers could attend to their traditional activity in rural areas without the loss of income. Besides, it is intended to provide results to help promote vegetable consumption. Research is focused on tomato, one of the main horticultural crops from the important agricultural region of South-Eastern Spain. The proposed solution for growers to improve profits is to cultivate traditional tomato varieties for local markets. Whether consumers are willing to pay the premium price for these products is analyzed and the influence of several attributes on willingness to pay is evaluated. To accomplish these aims, two methods have been used: a hypothetical method, the contingent valuation, and an experimental method, the Vickrey auction. Results show that local market consumers very positively value these varieties and are willing to pay very high premium prices, especially for the traditional flavour from their own area of influence.